Coordination mechanism of the three-echelon supply chain of fresh agriproduct with joint efforts - Wu, Jun; Jia, Wenpeng; Ba, Yile; Liu, Xin; Zhang, Yunbo; Li, Jian (Frontiers in Sustainable Food Systems, 2023)
Nowadays, the freshness level of agriproducts has become one of the major concerns for consumers. The demand for fresh agriproducts in the market has been increasing more than ever. However, the circulation losses of fresh agriproducts is significant during logistic processes, such as long-distance transportation. Statistics show that 20–25% of perishable agriproducts deteriorate in the circulation loop in developing countries, whereas in developed countries, this can be controlled at <5%. Developing countries must improve their cold-chain logistics and reduce post-production losses of this kind of agriproduct. The freshness-keeping effort for fresh agriproducts and the coordination mechanism of the supply chain have become two of the hot topics in this field. Based on the existing research, this study describes the freshness-keeping effort as a joint effort function of the supplier and the manufacturer, and studies the optimization and coordination of a three-echelon fresh agriproduct supply chain. In this research, four decision-making scenarios are modeled and analyzed, including decentralized decision-making, centralized decision-making, and two kinds of collaborative decision-making. Then, the profit distributions of two collaborative decision-making scenarios and centralized decision-making scenarios are calculated using the average tree solution. The study suggests that different cooperation styles of enterprises in the agriproduct supply chain have a different impact on the freshness level of the final product received by consumers. Both the final freshness level and the price of the product depend on the joint freshness-keeping efforts of the supplier and the manufacturer. The cooperation of enterprises in the three-echelon fresh agriproduct supply chain is conducive to the improvement of the final freshness level of agriproducts and the maximization of the supply chain's total profit. In such a three-echelon fresh agriproduct supply chain, the use of average tree solution can effectively distribute the profit and promote cooperation among different parties.